2019
DOI: 10.1002/jcp.28093
|View full text |Cite
|
Sign up to set email alerts
|

miR‐210 promotes lung adenocarcinoma proliferation, migration, and invasion by targeting lysyl oxidase‐like 4

Abstract: Accumulating evidence has revealed that various microRNAs are deregulated and involved in lung cancer development and metastasis. miR‐210 is implicated in several cancer progression. However, the detailed biological function and role of miR‐210 in lung adenocarcinoma remains unclear. Our current study was aimed to investigate the mechanism of miR‐210 in lung adenocarcinoma progression. We observed that miR‐210 was significantly upregulated in lung cancer cell lines (A549 and H1650) in comparison to BEAS‐2B cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…MiRNAs are known to downregulate gene expressions by base-pairing with the 3′-UTR of targeted mRNAs [22]. For example, mirR210 promoted lung adenocarcinoma proliferation and metastasis by targeting LOXL4 [23]. MiR-342 regulated breast cancer progression via modulating ID4 [24].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are known to downregulate gene expressions by base-pairing with the 3′-UTR of targeted mRNAs [22]. For example, mirR210 promoted lung adenocarcinoma proliferation and metastasis by targeting LOXL4 [23]. MiR-342 regulated breast cancer progression via modulating ID4 [24].…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐210 is an important regulator of various tumors, and aberrant miR‐210 expression has been identified in a variety of tumors. MiR‐210 facilitated lung adenocarcinoma growth, invasion, and metastasis via regulation of targeting lysyl oxidase‐like 4 36 . Up‐regulation of miR‐210 inhibited glioma cell growth and enhanced apoptosis through regulating switch‐insensitive 3 transcription regulator family member A (SIN3A) 37 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-210 is one of the most widely studied miRNAs and has captured great attention since it has been shown to be associated with various biological processes and the development of different human diseases thus far [44]. The increasing literatures exploring the role of circulating miR-210 in LUAD have been proved miR-210 to be a noninvasive biomarker for LUAD detection [45][46][47]. In Tamiya H's research, it revealed the AUC value of exosomes miR-210 in the diagnosis of LUAD combined with pleural effusion was 0.81 [48].…”
Section: Discussionmentioning
confidence: 99%